Analisis Biaya Penyakit Stroke Pasien Jaminan Kesehatan Nasional di RSUD Blambangan Banyuwangi - Zulfa Mazidah; Nanang Munif Yasin; Susi Ari Kristina (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Cost analysis of chronic diseases in health care facilities during JKN is needed as quality and cost control. Stroke is a high cost, volume, and risk, catastrophic disease that can cause an increase in medical expenses, which requires special attention. The purpose of this study is to provide an overview of real costs and cost components, providing an overview of the direct medical costs and tariff packages of INA-CBGs based on the type of stroke, and the factors that affect direct medical costs. This study is a descriptive-analytic observational study according to the hospital perspective. Data was taken retrospectively. The subjects of the study were adult JKN patients who were aged ≥18 years old with a stroke diagnosis that entered the inclusion criteria. The research variables included age, gender, type of stroke, comorbidity, hospitalization class, length of stay (LOS), and real costs. Data analysis used univariate, bivariate and multivariate analysis. The research results obtained total real costs of Rp. 1,525,236,503 with an average cost of Rp. 4,872,960, the largest cost component was the cost of drugs and BMHP Rp. 402,248,555 (27.21%). The real cost of hemorrhagic strokes is Rp. 572,969,865 and the INA-CBGs tariff package is Rp. 483,804,000, the real cost of ischemic stroke is Rp. 1,107,055,700. There were significant differences in real cost from class factors and length of stay (p-value <0.005). The concluded that the INA-CBGs tariff package is insufficient to finance hospitalized patients with hemorrhagic strokes (-Rp89.165,865), but sufficient for ischemic stroke (+Rp.154,789,069).